Peningkatan Motivasi Belajar dengan Strategi Jigsaw Learning pada Materi Puasa - Amin, Amin (MGMP PAI SMP BINTAN, 2023)
This research aims to determine students' learning motivation through the application of the jigsaw learning method in class VIII of junior high school. As educators, it is hoped that they will continue to improve their pedagogical competence in the learning process. one way is to apply more varied and innovative learning methods. This research is classroom action research. The subjects of this research were 33 class VIII SMP students. The research was carried out in 2 cycles. Based on the research results, it shows that the application of the jigsaw learning method in Islamic Religious Education subjects, fasting material in class VIII of junior high school has been proven to be able to increase students' learning motivation significantly. So that it can be used for the learning process in the future.